A Semantic Analysis of the Words 'Afuw' and 'Gafūr' in the Qur'an: The Perspective of Muhammad Syahrur's Anti-Synonymy Theory - Nisha Luthfia; Nur Aini; Abdul Jabpar (Lembaga penelitian dan pengabdian kepada masyrakat, 2025)
This study aims to examine the difference in meaning between the terms ‘afuw and gafūr in the Qur’an by employing Muhammad Syahrur’s theory of non-synonymy. The purpose of this research is to understand the foundational factors underlying Syahrur’s non-synonymy theory and to explore the implications of applying this framework to two Qur’anic terms that are commonly considered synonymous. The research method uses semantic analysis, which is then connected to Syahrur’s theoretical perspective on non-synonymy. The findings ultimately support Syahrur’s theory. The analysis of the Qur’anic usage of ‘afwu and gafūr reveals a clear differentiation in meaning between the domains of social ethics and the theological dimension of divine forgiveness. The terms ‘afwu and gafūr differ in the vertical and horizontal relational dimensions: ‘afwu operates within horizontal human relations, whereas gafūr pertains to vertical divine-human relations, giving each term complementary ethical and spiritual functions. In addition, the two terms differ in their inclusivity and exclusivity regarding the scope of forgiveness. This distinction has significant implications for the development of Islamic social ethics and deepens the understanding of God’s mercy and forgiveness.